2015
DOI: 10.1016/j.cell.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-Mediated Human 3D Genome Architecture Reveals Chromatin Topology for Transcription

Abstract: Summary Spatial genome organization and its effect on transcription remains a fundamental question. We applied an advanced ChIA-PET strategy to comprehensively map higher-order chromosome folding and specific chromatin interactions mediated by CTCF and RNAPII with haplotype specificity and nucleotide resolution in different human cell lineages. We find that CTCF/cohesin-mediated interaction anchors serve as structural foci for spatial organization of constitutive genes concordant with CTCF-motif orientation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

67
1,118
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 894 publications
(1,206 citation statements)
references
References 32 publications
(44 reference statements)
67
1,118
1
3
Order By: Relevance
“…Indeed, it has been recently observed that in chromatin loops formed by convergent CBS (convergent loops), forward and reverse CBSs are strongly associated with forward and reverse TSS, respectively, and TSS peaks are preferentially located downstream of the forward CBS and upstream of the reverse CBS. 17 One may note that the above-proposed interpretation of the extrusion model of TAD formation makes this model similar to the facilitated tracking model of enhancer-promoter communication. Indeed, this model postulates that PolII bound to the enhancer is able to bring it to the promoter via looping of an intervening DNA fragment that should occur in the course of transcription elongation.…”
Section: Hierarchical Folding Of the Eukaryotic Genome Within The Celmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, it has been recently observed that in chromatin loops formed by convergent CBS (convergent loops), forward and reverse CBSs are strongly associated with forward and reverse TSS, respectively, and TSS peaks are preferentially located downstream of the forward CBS and upstream of the reverse CBS. 17 One may note that the above-proposed interpretation of the extrusion model of TAD formation makes this model similar to the facilitated tracking model of enhancer-promoter communication. Indeed, this model postulates that PolII bound to the enhancer is able to bring it to the promoter via looping of an intervening DNA fragment that should occur in the course of transcription elongation.…”
Section: Hierarchical Folding Of the Eukaryotic Genome Within The Celmentioning
confidence: 83%
“…There is strong evidence for the participation of CTCF in the formation of TAD borders. 9,11,17 This may be a consequence of separate TAD assembly by self-compaction of extruded DNA loops. [18][19][20] The "loop extrusion" model postulates that TADs in mammalian genomes could be formed due to the energy-dependent pulling of the chromatin fiber through the "extrusion machine" resulting in the loop formation between convergent CTCF-binding sites (CBS) within this machine and folding of the looped fragment into a TAD (Fig.…”
Section: Hierarchical Folding Of the Eukaryotic Genome Within The Celmentioning
confidence: 99%
“…В последние годы с использованием технологий Hi-C и родственных методов получены новые знания об особенностях трёхмерной архитектуры (укладки) генома человека в интерфазном ядре клетки, влияющих на регуляцию экспрессии генов [7,8,9]. Рассматриваются вопросы формирования топологических доменов, выделения петель, формируемых контактами когезина и фактора CTCF [10]. Для обработки большого объёма данных ChIA-PET и Hi-C, развиваются компьютерные инструменты анализа, позволяющие получить качественно новую информацию о различных аспектах структурной организации генома [11].…”
Section: Introductionunclassified
“…Global analysis of long-range chromatin interactions using Hi-C has been achieved at kilobase resolution but requires billions of sequencing reads [8]. High-resolution analysis of long-range chromatin interactions at selected genomic regions can be attained cost-effectively through either ChIA-PET [7,9] or targeted capture and sequencing of Hi-C libraries [10]. ChIA-PET has been used to identify long-range interactions at promoters and enhancers at high resolution in various cell types and species [11].…”
mentioning
confidence: 99%
“…To reduce the amount of input materials and improve the sensitivity and robustness of the assay, we developed Proximity Ligation-Assisted ChIP-seq (PLAC-seq), in which proximity ligation is conducted in nuclei prior to chromatin shearing and immunoprecipitation ( Figure 1A, Supplementary information, Figure S1A and Data S1). We demonstrated that by switching the order of proximity ligation and chromatin shearing steps, PLAC-seq greatly improves the efficiency and accuracy over ChIA-PET [7,9] in detection of long-range chromatin interactions in mammalian cells.…”
mentioning
confidence: 99%